Bank funding liqudity, adjustment speeds of net stable funding requirement and risk-taking in BRICS - Dahir, Ahmed Mohamed (2019)
The conjecture that Basel III Net Stable Funding Ratio (NSFR) limits maturity mismatch problem and improves financial stability has strong intuitive appeal; however, the researcher’s knowledge with regards to the empirical support corroborating multi-faceted potential adjustment dimensions to assess banks’ response to tougher liquidity requirements and the link between NSFR and bank risk-taking has been tenuous at best. In this light, the study develops a comprehensive theoretical framework which posits that a better understanding of the relationship between NSFR and bank risk-taking is necessary, in order for the emerging economies to develop strategies that maintain sufficient liquidity holdings reducing the impacts of risktaking incentives and ensuring the credit supply. Guided by this framework, the study also investigates the adjustment speeds of banks in Brazil, Russia, India, China and South Africa (BRICS) toward target NSFR, the joint impact of NSFR and capital on bank risk-taking, the impact of funding liquidity on bank risk-taking and the interrelationship between NSFR and capital using a sample of 269 banks and unbalanced panel data for period 2006-2015. A set of econometric estimations, such as LSDVC, GMM and panel VAR is employed in order to perform the analysis. The results reveal that banks adjust quickly their target NSFR, but concordance is strongest for large banks suggesting that large banks actively manage their liquidity during the sample period. The bank risk-taking is inversely associated with NSFR and capital, indicating that NSFR and capital jointly reduce bank risk-taking incentives and, in turn, improve the financial stability of banking system; nevertheless, this is true only in case of large banks. Further, the bank risk-taking is positively related to funding liquidity. The findings appear to be conditional on bank regulation and supervision. Interestingly, strengthening of bank regulation and supervision mitigate the adverse effects of funding liquidity and weaken the linkage between NSFR and bank risk-taking behavior, showing that the NSFR and bank regulation and supervision appear to be substitutes rather than complements. Finally, Granger causality is found to exist between NSFR and regulatory capital; specifically, a unidirectional causality that runs from NSFR to capital. Unsurprisingly, banks have taken less risks during the recent financial crisis. Notably, the findings are robust to alternative estimations and different measures as well. The findings of the study have significant implications for bank regulators, policy makers and academics, emphasizing the importance of higher liquidity holdings and supporting the need to develop and implement long-term liquidity policies in order to effectively address the effects of potential financial turbulences in emerging economies, thereby setting bank safety and soundness. The results also justify the exemption of small banks from implementing Basel III new liquidity. The study is limited to BRICS economies, further work is needed to explore the effects of NSFR adjustment on bank outcome in BRICS and other developing and developed economies.